P14.68 Life expectancy in biopsied GBM patients: a single-centre experience. (6th September 2019) - Kalita, O; Sporikova, Z; Halaj, M; Cwiertka, K; Vaverka, M; Hrabalek, L; Trojanec, R; Hajduch, M; Drabek, J; Vrbkova, J
Abstract: BACKGROUND: The prognosis for patients with GBM remains dismal. The most aggressive multimodal therapy (maximally radical and safe tumour resection, followed by the Stupp protocol oncotherapy) has yielded the best treatment outcomes. Only a small proportion of patients initially undergo brain tumour biopsy. Our aim is to evaluate therapy results of biopsied GBM patients. MATERIAL AND METHODS: We followed all glioma patients from June 1, 2006. Information on surgeries, patient clinical condition, imagings, and results of histological, immunohistochemical, molecular genetic, and cytogenetic investigations was gathered. For this study, we selected a group of biopsied GBM patients in a period from June 1, 2006 to December 31, 2016. Needle biopsy (stereotactic, or navigated) was advised for unresectable tumours, for patients with unfavourable clinical conditions (KS<60), and for older patients (with age being the only surrogate criterion). Whenever possible, the patients were recommended Stupp protocol oncotherapy. Clinical and MRI follow-up after surgery was carried out (OS, PFS) until the patient's demise. RESULTS: Sixty adult GBM patients (27 females and 33 males) with their age ranging from 30 to 85 years old and with a mean age of 66.8 years were enrolled in this study. The diagnosis of GBM was established by biopsy. Fourteen of them (23%) had radiotherapy only. Five patients (8%) were able to receive the Stupp protocol oncotherapy. Forty-one patients (69%) had an unfavourable physical condition which was a contraindication to radiotherapy or chemotherapy, respectively. The average OS was 3.8 months. A limited number of samples were available for IDH status investigation. All of the seventeen GBMs were IDH wild-type. CONCLUSION: The initial surgical treatment strategy in GBM patients must be in the hands of an experienced neurosurgeon. Biopsy is required even when no further tumour-specific therapy is recommended. Regardless of the treatment strategy (resection or biopsy), multisite tumour sampling should be acquired. In our opinion, a decision to perform needle biopsy should be restricted to patients with unfavourable clinical conditions (age, KS, comorbidities, etc.), to large and deep-located brain tumours very often involving midline structures (corpus callosum, thalamus, basal ganglia), and to older patients. In accordance with these principles, we selected a small GBM patient group (12% of all GBM patients) with very limited life expectancy. The rationale for brain tumour biopsy is prevention of histological misdiagnosis and collection of biomarker data. But only the limited size of the tissue samples obtained was a significant obstacle to comprehensive cytogenetic investigation. We also recommend not to include biopsied GBM patients in studies with patients who had a radical resection. Supported by Ministry of Health of the Czech Republic, grant nr. NV19-04-00281.